PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Sindi Dwiroro Pangestu; Yunan Surono (Universitas Batanghari Jambi, 2017)
The research was done in the agricultural sector listed on the indonesian stock period 2011-2014 .The agricultural sector is a company that their activities trying to establish a certain plants on land or media all other plants .The agricultural sector listed on the efek indonesia which is there are 16 company where who was elected to the sample is purposive sampling , then become a sample in this research was as much as 4 companies are as follows: PT. Astra Argo Lestari Tbk, PT. Jaya Agra Wattie Tbk, PT. PP London Sumatra Indonesia Tbk, and PT. Salim Ivomas Pratama Tbk. The methodology be done in descriptive analysis and use the regression analysis multiple linear using spss 22 and statistic asumsition clasic test. The done is the hypothesis F test and the t test. and know to determine how much the determination (R2). Based on the results of this research suggests that in simultan between Return On Assets (ROA), Debt Asset Ratio (DAR) and Dividends Payout Ratio (DPR) significant Price Book Value (PBV) because f test larger than f tabel of 18,190 > 3,49 and the standard significant numbers (sig) of 0,000 < 0,05 so that it can be said to exist a positive influence .While in partial only Dividend Payout Ratio (DPR) that influence the Price Book Value (PBV) because t test greater than t table of 2,798 > 2,179. The value of the determination (R2) of 82% influenced by Return On Assets (ROA), Debt Asset Ratio (DAR), and Devidend Payout Ratio (DPR) the dominant significant Price Book Value (PBV) of 18% influenced by other factor. And only Dividend Payout Ratio (DPR) a variable dominant significant Price Book Value (PBV) as much as 2,798 >2,179. So Ho been denied and Ha accepted, it means have had a positive impact significantly on variables Price Book Value (PBV) in the agricultural sector listed on the efek indonesia the period 2011 -2014.Keywords: an investment decision , the funding , dividend policy , and value of enterprise.